Serum Levels of Mannose-Binding Lectin in Atopic and Healthy Mongolian Adults - Narantsogt, Giimaa; Mundur, Burnee; Enkhbaatar, Zanabazar; Dogsom, Oyungerel; Enkhbayar, Saruul; Gunregjav, Nyamaa; Tsogjargal, Urantsetseg; Dashdendev, Narmandakh; Agvaandaram, Gurbadam; Im, Kyung-il; et al. (Central Asian Journal of Medical Sciences, 2017)
Objectives: Mannose-binding lectin (MBL) is a vital protein of an innate immune system synthesized by the liver. The serum level of MBL is associated with an increased susceptibility to infection with a high risk of allergic and autoimmune diseases. The aim of this study was to determine the profile of serum levels of MBL in atopic and healthy Mongolian subjects. Methods: Serum samples were collected from 219 healthy Mongolian adult blood donors and 216 atopic subjects. We analyzed the MBL level in each serum by using the double-antibody sandwich ELISA method. Results: The mean serum level of MBL was 3088.28 ± 669.8 ng/ ml in atopic subjects and 2165.07 ± 708.5 ng/ml in healthy groups. In males, the MBL mean serum level of atopic subjects was 3012.8 ± 783.16 ng/ml and 2073.33 ± 678.26 ng/ml in the healthy group of males. The MBL mean serum level of female atopic subjects was 3138.22 ± 580.6 ng/ml and 2263.61 ± 733.1 ng/ml in the healthy group of females. Low association and significant differences were observed between MBL levels of atopic and healthy subjects. Conclusion: The serum level of MBL in atopic subjects was comparatively higher than in subjects of the healthy group. Significant differences were observed between mean levels of MBL between the different age groups.